The African Union as a human security actor: a study of the AU mission to Somalia (Amisom) from 2007-2017 - van Der Merwe, Reon Carel Aron (Department of Political Studies, 2023)
This thesis assesses the effectiveness of the African Union as a pro-human security actor in conflict. It employs a case study approach using the AU Mission in Somalia (AMISOM) from 2007-2017 to examine the extent to which the AU has helped, hindered or harmed human security through its interventions. A critical human security lens is used to unpack the organisation's efficacy in anticipating, mitigating and responding to both direct and indirect forms of violence faced by civilians. This study relies primarily on secondary qualitative data sources including policy documents, mission reports and interviews with Somali civilians, government officials and ex-combatants. The data shows that AMISOM experienced mixed results in its ability to proactively account for and respond to the human security needs of Somali citizens. This is due to several factors, including its overreliance on third party forces, inconsistent access to resources to match extensive mandates and the organisation's propensity toward state-centric forms of interventionism. The study finds that in some cases AMISOM was able to evolve and adapt to minimise its own direct contributions to human insecurity over time. However, the AU-led mission remained largely reactive and in some cases enabled, indirect drivers of insecurity facing Somali citizens.